Problematika Implementasi Kurikulum Merdeka di SMP Negeri 5 Padang Panjang - Susanti, Hendra; Fadriati, Fadriati; B.S, Iman Asroa (ALSYS, 2023)
This research was conducted with the aim of knowing and describing the problems of implementing the independent curriculum that occurred at SMPN 5 Padang Panjang. This research departs from the background of the many phenomena surrounding the implementation of the independent curriculum and various policies regarding the independent curriculum. The research question raised is how the problems of implementing the independent curriculum at SMPN 5 Padang Panjang are problematic. The research was conducted with a qualitative type of field research. Data was collected by interviewing school principals, curriculum representatives, and teacher councils as well as making observations at SMPN 5 Padang Panjang. The results of these interviews were analyzed and then presented in a descriptive form. The results of this analysis can answer the questions formulated in the research questions. The results of this analysis are in the form of problems in the implementation of the independent curriculum originating from the government in the form of less than optimal guidance and assistance in the implementation of the independent curriculum. In addition, there are also problems originating from teachers in the form of a lack of teacher ability to utilize independent teaching platforms and utilize technology to learn and understand independent curriculum.